2022
DOI: 10.7860/njlm/2022/53615.2617
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Associated Tissue Eosinophilia in Oral Squamous Cell Carcinoma by Special Histochemical Analysis of Tissue Eosinophilia using Congo Red Staining

Abstract: Introduction: Tumour Associated Tissue Eosinophilia (TATE) is an important phenomenon occurring in the tumour microenvironment and has a pivotal role. TATE is defined as “eosinophilic stromal infiltration of a tumour not associated with tumour necrosis or ulceration”. The exact role of TATE in malignancies is yet unclear but studies have shown that TATE usually has a favourable outcome in head and neck Squamous Cell Carcinoma (SCC). Therefore, more studies are needed to substantiate this data. Aim: To compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The actual mean of MPV was highly significantly (P<0.0001) increased compared with theoretical mean, in the diagnosis of acute appendicitis, MPV level was not a reliable indicator and this computable with (Akbulut et al, 2019, Dooki et al, 2022. In contrast with (Tanrikulu et al, 2014, Tullavardhana et al, 2021 they reported decreased MPV in acute appendicitis patients. Presence of inflammatory cells such as eosinophil within the wall of the appendix is required for histological diagnosis of AEA which diagnosed by edema infiltration of muscularis layer by eosinophils, so the gold standard for the diagnosis of AEA is still histopathology analysis and these can be demonstrated by different routine & special stains (Kinoshita et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The actual mean of MPV was highly significantly (P<0.0001) increased compared with theoretical mean, in the diagnosis of acute appendicitis, MPV level was not a reliable indicator and this computable with (Akbulut et al, 2019, Dooki et al, 2022. In contrast with (Tanrikulu et al, 2014, Tullavardhana et al, 2021 they reported decreased MPV in acute appendicitis patients. Presence of inflammatory cells such as eosinophil within the wall of the appendix is required for histological diagnosis of AEA which diagnosed by edema infiltration of muscularis layer by eosinophils, so the gold standard for the diagnosis of AEA is still histopathology analysis and these can be demonstrated by different routine & special stains (Kinoshita et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…In contrast RDW indices have been reported for identifying acute and perforated appendicitis (Haghi et al, 2020). Also (Tartar et al, 2020) reported a high level of RDW in complicated cases.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation